Pattern of tooth mobility in smokers and non-smokers with chronic periodontitis - PARTHASARATHY, PREETHA; JEEVITHA, M.; DHARMAN, SREEDEVI (The journal of contemporary issues in business and government, 2021)
Periodontitis is an infectious inflammatory disease that is caused by the bacteria of dental plaque resulting in the progressive destruction of the tissue supporting the teeth, that is gingival, periodontal ligament, cementum and the alveolar bone. The progression of the disease is accelerated by tobacco consumption. The aim of this study is to find the pattern of tooth mobility in smokers and non smokers. This retrospective study was conducted in a Private dental college, chennai. The sample size was 100, with 50 smokers and 50 non smokers. The data was collected from the hospital digital database. It was observed that tooth mobility in smokers was prevalent in the posterior region (16%) (p<0.05) and in the maxilla and both the jaws (11% & 23% respectively). Tooth mobility in smokers was commonly seen in the posterior region of maxilla (10%) and anterior region of mandible (20%) for which the P value was found to be statistically significant (<0.05). For non-smokers, there was an increased tooth mobility observed in the anterior region of the mandible (34%) for which the P value was found to be statistically significant (<0.05). Within the limits of the study, it can be concluded that smoking causes increased periodontal destruction to the surrounding tissues, with tooth mobility and loss commonly observed in the posterior regions of maxilla and posterior region in both the jaws. Thus, Progression of disease can be prevented by early diagnosis and by tobacco cessation programmes.